Unveiling The Healing Power of Argyreia Nervosa: A Deep Dive into Its Pharmacological Activity for Cough and Asthma Relief - Sharma, Arun Kumar; Rai, Janki Prasad (Journal of Neonatal Surgery, 2025)
Argyreia nervosa is employed in various medicinal traditions. A. nervosa showcases a diverse array of pharmacological properties, spanning from antimicrobial, antipyretic, anti-inflammatory, and immunomodulatory potential and hepatoprotective to nootropic and anticonvulsant effects. The present study focused on the healing power of this species for cough and asthma disease by evaluating its antitussive (cough suppressant) and expectorant (mucus-clearing) activities on animal models of coughing. The expectorant activity was also evaluated by measuring the amount of phenol red secretion in the trachea of mice. Acute bacterial bronchitis model was also created by treating mice with Streptococcus pneumoniae and Serum superoxide dismutase and malondialdehyde levels were measured to find oxidative stress. Both the aqueous extract and polysaccharides, administered at high doses (600mg/kg), notably suppressed the frequency of cough induced by sulfur dioxide in mice during the antitussive tests. However, only polysaccharide (600mg/kg) was effective and inhibited 55.3% of coughing in the ammonia-induced coughing test at a high dose. The polysaccharides (600mg/kg) significantly enhanced the tracheal phenol red output (87.36%) compared to the control group, indicating their expectorant effects. Higher level of SOD and lower levels of MDA in acute bacterial bronchitis model confirms the effectiveness of A. nervosa further. This study suggests that A. nervosa could be a valuable natural alternative to synthetic drugs for cough and asthma treatment